2013
DOI: 10.3402/gha.v6i0.18857
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related harm among university students in Hanoi, Vietnam

Abstract: Introduction and AimThis study examines the prevalence of and risk factors for alcohol-related harm and types of harm among medical students from Hanoi Medical University (Vietnam). Risk factors include aspects of drinking patterns and relevant socio-demographic variables.Study Design and MethodsA cross-sectional study involving 1st to 6th year students (N=1216; response rate 96.5%). Of these, 210 students from each academic year were randomly selected from a sampling frame covering all students from each acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Previous research documented a peak of risktaking behavior (e.g., alcohol and drug use; unprotected sex; risky driving behavior) among the U.S. young adults during their transition to independent living (Bowers, Segrin, & Joyce, 2016;Kypri, McCarthy, Coe, & Brown, 2004). Likewise, Diep et al (2013) found that living away from home was a strong predictor of alcoholrelated harm among Vietnamese college students in Vietnam. Discussing this phenomenon, Arnett stated that less parental control and greater friend influence allowed emerging adults to engage in risktaking more freely than adolescents.…”
Section: Theoretical Perspectivementioning
confidence: 95%
See 1 more Smart Citation
“…Previous research documented a peak of risktaking behavior (e.g., alcohol and drug use; unprotected sex; risky driving behavior) among the U.S. young adults during their transition to independent living (Bowers, Segrin, & Joyce, 2016;Kypri, McCarthy, Coe, & Brown, 2004). Likewise, Diep et al (2013) found that living away from home was a strong predictor of alcoholrelated harm among Vietnamese college students in Vietnam. Discussing this phenomenon, Arnett stated that less parental control and greater friend influence allowed emerging adults to engage in risktaking more freely than adolescents.…”
Section: Theoretical Perspectivementioning
confidence: 95%
“…The U.S. Census Bureau (2018) estimated that around 65% of U.S. young adults from 18 to 24 years of Nguyen and Soysa | Eating Pathology in Vietnamese and Americans age occupied college dormitories, cohabitated with their friends or unmarried partners, or lived alone. Interestingly, Vietnamese college students reported similar rates of living independently from parents, suggesting that the conceptual framework of emerging adulthood may not be unique to the U.S. population of young adults (Diep, Knibbe, Giang, & De Vries, 2013). Given that we studied a group of international Vietnamese undergraduates in the United States, we expected an even higher rate of cohabitation with nonrelatives or friends among this group of students.…”
Section: Theoretical Perspectivementioning
confidence: 98%
“…Previous research documented a peak of risktaking behavior (e.g., alcohol and drug use; unprotected sex; risky driving behavior) among the U.S. young adults during their transition to independent living (Bowers, Segrin, & Joyce, 2016;Kypri, McCarthy, Coe, & Brown, 2004). Likewise, Diep et al (2013) found that living away from home was a strong predictor of alcoholrelated harm among Vietnamese college students in Vietnam. Discussing this phenomenon, Arnett stated that less parental control and greater friend influence allowed emerging adults to engage in risktaking more freely than adolescents.…”
Section: Theoretical Perspectivementioning
confidence: 96%
“…A large number of young adults share housing with their friends and/or their romantic partners during their college years (Arnett, 2000 age occupied college dormitories, cohabitated with their friends or unmarried partners, or lived alone. Interestingly, Vietnamese college students reported similar rates of living independently from parents, suggesting that the conceptual framework of emerging adulthood may not be unique to the U.S. population of young adults (Diep, Knibbe, Giang, & De Vries, 2013). Given that we studied a group of international Vietnamese undergraduates in the United States, we expected an even higher rate of cohabitation with nonrelatives or friends among this group of students.…”
Section: Theoretical Perspectivementioning
confidence: 98%
“…In their study, Giang et al report on common problems related to alcohol consumption among men in Vietnam and report that the share of total household expenditure on alcohol is remarkable, especially among poorer households (12). Diep et al also suggest that alcohol-related harms present a serious public health problem among young and educated individuals (13). Linh et al (14) discuss the relationship between alcohol use and road traffic accidents, and Phuong et al (15) demonstrate the association between harmful use of alcohol and suicidal thoughts.…”
mentioning
confidence: 99%